Routing reserved bandwith multi-point connections. - Verma, Dinesh C.
Some important classes of multi-point bandwidth-intensive applications like video-conferencing with mixing and the distributed classroom can be characterized as consisting of a broadcast from a source node to several destinations nodes, and point-to-point flows from the destination nodes to the source node. Determining a tree in an arbitrary mesh network which satisfies the bandwidth constraints and minimizes the cost of reserved bandwidth is a NP-hard problem. In this paper, we look at some heuristics that can be used to solve the problem of routing these multi-point connections. The heuristics are based on finding the capacity-constrained minimum cost tree which minimizes the cost of bandwidth reserved for point-to-point communication from destinations to the source, and weights are assigned to minimize the number of extra nodes in the tree which increase the cost of bandwidth reserved from the source to the destination. A theoretical bound on the performance of some of the heuristics, as well as simulation results comparing their performance to that of the optimum solution are presented. The results are encouraging, the heuristics find a tree with a cost within 2% of the optimum on the average, and with a cost within 10% of the optimum in those cases when the heuristic fails to find the optimum tree.
Keywords: Computer systems organization; Computer communication networks; Theory of computation; Analysis of algorithms and problem complexity; Nonnumerical algorithms and problems; Routing and layout; Mathematics of computing; Discrete mathematics; Graph theory; Trees; Path and circuit problems; Information systems; Information systems applications; Communications applications; Computer conferencing; Teleconferencing; Videoconferencing; Design; Performance; Verification